EFEKTIVITAS PIJAT OKSITOSIN DAN BREAST CARE PADA IBU BERSALIN TERHADAP PENGELUARAN ASI DI PUSKESMAS KAMONJI - Hadriani, Hadriani; Hadati, Rahma (Window of Health : Jurnal Kesehatan, 2019)
Breastfeeding is one of the global health issues in the 21st century, given that breastfeeding has a significant effect on infant mortality. The absence of breastfeeding in the first days after giving birth is one of the reasons for not creating exclusive breastfeeding. The inhibition of breastmilk secretion can be caused by inhibition of oxytocin secretion which is very instrumental in smoothing out ASI expenditure. Stimulation of the hormone prolactin and oxytocin can be done through breast care and oxytocin massage. Kamonji Health Center is the health center with the lowest exclusive breastfeeding coverage in Palu City, which is 57.3%. The purpose of this study was to find out the comparative time of mother's milk delivery which was given oxytocin massage and breast care within 2 hours postpartum in the Kamonji Community Health Center work area. This study is a quasi-experimental study with the design of The posttest-only control group. The number of samples was 30 people, taken by consecutive sampling technique and divided by 15 respondents into the oxytocin and breast care massage groups. The intervention was carried out within 2 hours postpartum and then observed when the first ASI was discharged after the third stage ended. Data normality test using Shapiro-Wilk test, data analysis using Mann Whitney test obtained a significance value of 0.044, with the average time of mother's breastmilk given oxytocin massage was 14.19 hours and breast care 5.57 hours. The conclusion of the study is that there is a difference in the time of mother's milk to be given oxytocin massage and breast care in the fourth stage of labor. Based on the results of this study it is recommended to do breast care to help accelerate the release of breast milk.